Dating urban classical deposits : approaches and problems in using finds to date strata - Furlan, Guido (Archaeopress Archaeology, 2019)
Considers the dating of archaeological strata on the basis of the assemblages recovered from them. It reviews the present state of archaeological practice and follows this with a theoretical discussion of the key concepts involved in the issue of dating deposits.